Mixtures of mono-, di- and tri-glycerides as energy supplements to broilers’ diets - Sara Minieri (Italian Journal of Animal Science, 2010)
Mixtures of mono-, di- and tri-glycerides from olive oil (MDT) were added to: palm oil (PO), olive oil (OO), soybean oil (SO), free fatty acids from palm oil (PFA), free fatty acids from olive oil (OFA). The compound mixtures were used as energy supplements in the diets of broiler chickens in comparison with plain SO and plain animal fat (AF). Two hundred and ten birds were randomly allotted to 7 dietary treatments with the diverse oil sources: 6 birds per cage, 5 cages per treatment. The effects of the treatments on growth rates, feed/gain ratios and acidic composition of abdominal fat of hybrid Ross 308 female chickens were studied. The animals were slaughtered at the end of the trial, at day 35. The breast meat quality was then evaluated by a panel of 15 trained members and analysed for shelf life duration. The AF treat- ment gave the highest weight gain, but only in the first week. MDT + OO (50/50) resulted the best combination, with slight, non significant, better performances and a decidedly better quality in terms of acidic composition of abdominal fat, taste and juiciness of breast meat and shelf life.